Sodium Fluxes through Nonselective Cation Channels in the Plasma Membrane of Protoplasts from Arabidopsis Roots - Demidchik, Vadim (American Society of Plant Biologists, 2002)
The aim of the present work was to characterize Na(+) currents through nonselective cation channels (NSCCs) in protoplasts derived from root cells of Arabidopsis. The procedure of the protoplast isolation was modified to increase the stability of Arabidopsis root protoplasts in low external Ca(2+) by digesting tissue in elevated Ca(2+). Experiments in whole-cell and outside-out modes were carried out. We found that Na(+) currents in Arabidopsis root protoplasts were mediated by cation channels that were insensitive to externally applied tetraethylammonium(+) and verapamil, had no time-dependent activation (permanently opened or completely activated within 1–2 ms), were voltage independent, and were weakly selective for monovalent cations. The selectivity sequence was as follows: K(+) (1.49) > NH(4)(+) (1.24) > Rb(+) (1.15) ≈ Cs(+) (1.10) ≈ Na(+) (1.00) > Li(+) (0.73) > tetraethylammonium(+) (0.47). Arabidopsis root NSCCs were blocked by H(+) (pK ≈ 6.0), Ca(2+) (K(1/2) ≈ 0.1 mm), Ba(2+), Zn(2+), La(3+), Gd(3+), quinine, and the His modifier diethylpyrocarbonate. They were insensitive to most organic blockers (nifedipine, verapamil, flufenamate, and amiloride) and to the SH-group modifier p-chloromercuriphenyl sulfonic acid. Voltage-insensitive, Ca(2+)-sensitive single channels were also resolved. Properties of Arabidopsis root NSCCs are discussed and compared with characteristics of similar conductances studied previously in plants and animals. It is suggested that NSCCs present a distinct group of plant ion channels, mediating toxic Na(+) influx to the cell and probably having other important roles in physiological processes of plants.